Correlation Beetween Motivation and Supervision on Completeness Filling Medical Resume by Doctor - Achmad Deza Farista; Aila Karyus (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2020)
Medical resume reflects all important information relating to patients, used as a basis for determining further action in the effort of medical services. Numbers for completing 2019 medical record documents at Pesawaran District Hospital are 43.33%, whereas for incomplete medical resumes are 37.4%. The purpose of this study was to find out the correlation between motivation and supervision of the completeness of filling medical resumes by doctors at Pesawaran District Hospital. This study used an observational design with a cross sectional approach. conducted in February - May 2020 at the Pesawaran District Hospital. The study population was all doctors involved in the inpatient service at Pesawaran District Hospital with a total of 37 doctors with the study sample being the total population, a total of 37 respondents. Data analysis for univariate use frequency distribution and for bivariate use the chi-quere test. There is relation of motivation with the completeness of filling medical resumes by doctors at Pesawaran District Hospital (p value 0.029. OR 6) and there is a relation of supervision with completeness of filling medical resumes by doctors at Pesawaran District Hospital (p value 0.022. OR 7.04) (α < 0.05).